Determination of Antioxidant Capacity and Polyphenols Contents in Fruits of Genotypes of Chaenomeles japonica (Thunb.) Lindl. - Klymenko, Svitlana; Kucharska, Alicja Zofia; Sokół-Łętowska, Anna; Piórecki, Narcyz (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
In traditional Chinese medicine, the fruits of various species of Chaenomeles Lindl. have been used for thousands of years in the treatment of rheumatoid arthritis, hepatitis, asthma, and the common cold and also have reported anti-inflammatory, antinociceptive, antimicrobial, antioxidant, immunoregulatory, antitumor, hepatoprotective, antiparkinsonian, and antioxidant activities. Fruits contain many bioactive components, including polyphenols, triterpenes, and organic acids. Cold-pressed Chaenomeles japonica (Thunb.) Lindl. seed oil is one of the richest sources of natural micro constituents such as fatty acids, carotenoids, squalene, polyphenols, phytosterols, tocopherols and other compounds with high biological activity. The aim of this work was to evaluate the biological activity of fruits of Chaenomeles japonica genotypes, as potential species for cultivation and use in Ukraine. The objects of the research were 13 genotypes of Chaenomeles japonica selection in M.M. Gryshko National Botanical Garden (Kyiv, Ukraine). The raw materials were collected in the season of full ripeness (October). Antioxidant activity (AOA) was measured using three different photometric methods (DPPH – 2,2-diphenyl-1-picrylhydrazyl, ABTS – 2,2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid, FRAP – ferric-reducing antioxidant power). Total polyphenol content (TPC) was evaluated using the Folin-Ciocalteu reagent assay. The results for AOA (μmol Trolox/g) determined by the DPPH method varied from 10.08 to 21.42, those obtained by the ABTS method varied from 31.13 to 70.87, and those obtained by the FRAP method varied from 14.97 to 42.51. The results for TPC varied from 162.46 to 408.09 mg/100 g. The results showed that all fruit extracts exhibited strong antioxidant activities, which generally correlated positively with the total phenol contents. Due to the content of biologically active substances, the fruits are valuable raw materials for various types of processing in the confectionery, distillery, pharmaceutical industries, production of natural low-calorie products for children, diet and treatment and prophylactic nutrition. This means that genotypes of Chaenomeles japonica may be used as a source of new health resources when improving the nutritional properties of the world’s less traditional fruit species.